ANALISIS KEUNTUNGAN USAHA RUMAH PANGGUNG CV SIVEL DI DESA MOKOBANG KECAMATAN MODOINDING KABUPATEN MINAHASA SELATAN (Analysis of Business Profits of Stilt House Business of â€œCV Sivelâ€ s in Mokobang Village, Modoinding District, Minahasa Selatan Regency) - Rizal Josua Lembong; Leonardus Ricky Rengkung; Ribka M. Kumaat (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2021)
This study aimed to analyze the profits of CV Sivel's "Rumah Panggung" in Mokobang Village, Modoinding District, South Minahasa Regency. The data used were primary data and secondary data and were analyzed by means of lesion profit analysis. The results showed that each of these businesses got a profit of Rp. 34,474,875 for the "30m2" type, Rp. 37,175,424 for the "63m2" type, and Rp. 58,069,767 for the "91m2" type.Keywords: Profit Analysis, Stilt Houses